The Role of Linguistics the Teaching of English in College - Yahmun Yahmun; Susanto Susanto; Adi Adi (IKIP Budi Utomo Malang, 2023)
Linguistics is the science of language that develops from time to time. The development of linguistics has an important role in teaching English. Students are expected to be aware of these developments and have knowledge of languages ​​so that they are able to find or apply suitable methods in teaching English when they become teachers later.